2021
DOI: 10.1101/2021.10.21.21265349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and Effectiveness of COVID-19 SPUTNIK V Vaccine in Dialysis Patients

Abstract: Given the vulnerability of people with chronic kidney disease to COVID-19, nephrology societies have issued statements calling for prioritization of these patients for vaccination. It is not yet known whether COVID-19 vaccines confer the same high level of protection in patients with kidney disease. The aims of this study were to evaluate the safety measured by the events supposedly attributed to vaccines and the effectiveness evaluated by the presence of antibodies in dialysis patients immunized with the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Data on short-term immunogenicity of the Gam-COVID-Vac vaccine in hemodialysis patients are limited, while long-term data are still lacking. Rosa-Diez et al investigated short-term antibody response after Gam-COVID-Vac immunization and found high seroconversion that reached 98% 21 days after complete vaccination [3]. We observed a similar seroconversion rate (91%), which was almost halved by 6th month, indicating a strong need of boost vaccination by this time.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Data on short-term immunogenicity of the Gam-COVID-Vac vaccine in hemodialysis patients are limited, while long-term data are still lacking. Rosa-Diez et al investigated short-term antibody response after Gam-COVID-Vac immunization and found high seroconversion that reached 98% 21 days after complete vaccination [3]. We observed a similar seroconversion rate (91%), which was almost halved by 6th month, indicating a strong need of boost vaccination by this time.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies evaluated the safety and e cacy of Gam-COVID-Vac in general population in both early and long-term period [1,2]. The vaccine immunogenicity in patients receiving maintenance hemodialysis (HD), which are known to be highly vulnerable immunocompromised population, has also been reported previously [3]. However, a lack of knowledge exists concerning long-term Gam-COVID-Vac e cacy in dialysis-dependent patients.…”
Section: Introductionmentioning
confidence: 99%
“…The seroconversion rate of our population under dialysis was similar to that reported by previous studies showing values between 80-98% [15-20-. Rosa-Diez (2021) detected a 98% seroconversion rate in a study including 102 dialysis patients vaccinated with the Sputnik V scheme [16-. On the other hand, studies performed on patients under dialysis conditions immunized with Moderna vaccines have shown seroconversion rates ranging between 95% and 97.9% [15-,18-,21-.…”
Section: Discussionmentioning
confidence: 99%
“…[6] La efectividad de la vacuna ha sido demostrada en diferente grado para la prevención y gravedad del cuadro, entre ellas CoronaVac (Sinovac Biotech), BNT162b2, (Pfizer-BioNTech), mRNA-1273(Moderna), AZD1222 (AstraZeneca), AD5-nCoV (Cansino), Ad26.CoV2S (Jannsen) y Gam-Covid-Vac (Sputnikv), a la par se ha identificado que las condiciones en torno a la población y las dosis de aplicación de la vacuna influyen en la efectividad, considerada esta como la prevención del cuadro o de casos graves que requieren hospitalización, en particular para prevenir hospitalización la efectividad reportada fluctúa entre 79 % y 98 %. [7,8,9,10,11] En este contexto el objetivo del artículo es evaluar el efecto protector de la vacuna para SARS-CoV-2 para hospitalizaciones por COVID-19 durante la cuarta ola epidémica en Querétaro, México.…”
Section: Introductionunclassified